Perlindungan Data Pribadi dalam Kasus Ransomware: Apa Kata Hukum? - Seri Mughni Sulubara (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Ransomware attacks are an increasingly complex and costly global threat. International reports show a 300% increase in the frequency of ransomware attacks in the last five years (for example, data from IBM Security or Kaspersky). This threat not only blocks data access through encryption, but also jeopardizes privacy. This research will also examine the criminal law aspects associated with ransomware attacks, including the possible prosecution of the perpetrators of the attacks and the legal liability for victimized organizations. The theoretical study in the research titled